FRI0005 Signal transducer and activator of transcription 3 regulates synovial inflammation through notch/hif1a pathways. (23rd January 2014) - Gao, W.; McCormick, J.; Connolly, M.; Veale, D.; Fearon, U.
Abstract : Background: Angiogenesis is one of the primary events in the pathogenesis of inflammatory arthritis. Notch/HIF signalling interactions regulate angiogenesis and endothelial cell (EC) fate in Rheumatoid Arthritis (RA), however the precise mechanisms involved remain to be elucidated. Objectives: To examine the role of signal transducer and activator of transcription 3 (STAT3) in mediating hypoxia/Notch-induced interactions and downstream functional pathways in RA. Methods: Phospho-STAT3 (p-STAT3) expression in RA synovial tissue was quantified by Immunohistology/Immunofluorescence and Western Blot. Notch-1 IC, HIF1α, p-STAT3 and total-STAT3 protein levels were assessed in RA synovial fibroblast cells (RASFC) and an immortalised synoviocyte cell line (K4IM) under normoxic and hypoxic (3%) conditions by Western Blot. Gene expression of the Notch-1 receptor, its ligand DLL-4 and downstream target genes ( hrt-1, hrt-2 ) were quantified by Real-time PCR. Migration, invasion, matrigel network formation and MMP2/9 in-gel zymography were quantified under normoxic and hypoxic (3%) conditions in the presence of STAT3 siRNA or STAT3 inhibitor (WP1066). Using RA synovial explants ex-vivo, the effect of the STAT3 inhibitor (WP1066) on IL-6, IL-8 and IL-10 expression were assessed by ELISA. Results: Nuclear expression of p-STAT3 was demonstrated in RA synovial tissue, localised to the sub-lining and lining layer regions. p-STAT3 expression was significantly higher in inflamed synovial tissue compared to normal synovial tissue. Hypoxia-induced p-STAT3, Notch-1 IC, HIF1α protein expression in RASFC and K4IM, an effect that was inhibited by the presence of STAT3 siRNA or WP1066. Similarly hypoxia-induced Notch-1 receptor, DLL-4 and hrt-1, hrt-2 gene expression were inhibited in the presence of WP1066. Functionally hypoxia-induced RASFC/K4IM invasion, matrigel network formation, migration, and pro-MMP-2/-9 activities, were inhibited in the presence of STAT3 siRNA and the STAT3 inhibitor. Finally we demonstrated in RA synovial explants ex-vivo that WP1066 significantly decreased IL-6, IL-8 expression and significantly increased anti-inflammatory cytokine IL-10 expression. Conclusions: This study demonstrates regulatory mechanisms between p-STAT3, HIF1α and Notch-1 signaling in RA. STAT3 blockade by siRNA or WP1066 inhibits pro-inflammatory pathways in RA, suggesting that STAT3 may be a potential therapeutic agent for the treatment of RA. Disclosure of Interest: W. Gao: None Declared, J. McCormick: None Declared, M. Connolly: None Declared, D. Veale Grant/research support from: Abbott, Opsona, Pfizer, Roche, Consultant for: MSD, Pfizer, Roche, Speakers bureau: Janssen, MSD, Pfizer, UCB, U. Fearon: None Declared